Embracing the Imperfectness of Nature using Highly Reactive N-Acyl Azahexatrienes - Zheng, Kuan; Zhang, Bingbing; Hong, Ran (Synlett, 2023)
Incredible examples of controlling highly reactive functional groups to synthesize amazing architectures can be found in nature. N-Acyl azahexatriene, which is involved in biosynthesis, is clearly among them, despite the extremely limited number of examples disclosed in the literature. We explored the biomimetic synthesis of macrocarbocyclic natural products, chejuenolides A–C, as well as structural variants, to unveil the hidden stereochemical relationships between their biosynthesis and those of lankacidin antibiotics. This revealed the logic of the reaction pattern, which was likely influenced by catalytic promiscuity in nature.
Keywords: antibiotic; biomimetic synthesis; chejuenolide; macrocyclization; Mannich